EFISIENSI KONSENTRASI PEREKAT TEPUNG TAPIOKA TERHADAP NILAI KALOR PEMBAKARAN PADA BIOBRIKET BATANG JAGUNG (Zea mays L.) - Asri Saleh (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
The aims of this research are determine differences influnce the concentration of adhesive to the combustion heating value and detremine the optimum heating value. The method is performed in this study is an experimental method. Data obtained from the analysis with use a bomb calorimeter, which is at a concentration of 10% adhesive produced calorific value 4100.350 cal/g, 20% of the calorific value of 3674,14 cal/g, 30% of the calorific value of 3689,52 cal/g, 40% of the calorific value of 3902,21 cal/g and at a concentration of 50% adhesive calorific value generated is 3959,02 cal/g. The results of statiscal analysis using the inferential Analysis of Variance (ANAVA), with F test, F arichimetic (0,168) < F table (5,19) at significant level α = 0,05 then H0 rejected it means tha there is no difference in the influence of the concentration of adhesive to the calorific value biobriquet burning corn stalks on.